Pregnancy Outcomes in Women With a History of Previable, Preterm Prelabor Rupture of Membranes. Issue 5 (November 2016) - Monson, Martha A.; Gibbons, Karen J.; Esplin, M. Sean; Varner, Michael W.; Manuck, Tracy A.
Abstract : OBJECTIVE: To characterize subsequent pregnancy outcomes among women with a history of previable, preterm prelabor rupture of membranes (PROM) and assess factors associated with recurrent preterm birth. METHODS: This was a retrospective cohort study of women cared for with a history of one or more singleton pregnancy complicated by preterm PROM at less than 24 weeks of gestation between 2002 and 2013 who were cared for in two tertiary care health systems by a single group of maternal-fetal medicine specialists. Women were identified using International Classification of Diseases, 9th Revision codes and obstetric databases. Those with iatrogenic preterm PROM and those whose index preterm PROM at less than 24 weeks of gestation was preceded by advanced cervical dilation were excluded. All women with one or more pregnancies reaching the second trimester after an index previable, preterm PROM pregnancy were included. The primary outcome was recurrent preterm birth at less than 37 weeks of gestation. Data were analyzed by χ 2, Fisher exact, t test, Wilcoxon rank-sum, and logistic regression. RESULTS: Two hundred ninety-four women had one or more pregnancies complicated by previable, preterm PROM. One hundred eight of 294 (37%) had one or more subsequent pregnancies in our health care systems and 50 of 108 (46%) had two or more. In the pregnancy immediately after the index delivery, the risk of prematurity was high: 50 (46%) delivered at less than 37 weeks of gestation, 31 (30%) at less than 34 weeks of gestation, 25 (23%) at less than 28 weeks of gestation, and 18 (17%) before 24 weeks of gestation. Fewer than half (n=49 [45%]) of women received preterm birth prophylaxis (progesterone or cerclage) in a subsequent pregnancy; rates of recurrent preterm birth were similar among women who received preterm birth prophylaxis compared with those who did not. In regression models, the only factor significantly associated with recurrent preterm birth at less than 37 weeks of gestation was a history of preterm birth preceding previable, preterm PROM delivery (adjusted odds ratio 3.23, 95% confidence interval 1.32–7.93). CONCLUSION: Patients with a history of previable, preterm PROM are at high risk of recurrent preterm birth. Abstract : Women with a history of previable, preterm prelabor rupture of membranes are at high risk for preterm birth and previable delivery in subsequent pregnancies.